A platinum-carbon catalyst and preparation method thereof

By using ultraviolet irradiation and heat treatment in the microflower, the platinum salt is reduced in stages and supported on the carbon support, solving the problem of platinum carbon catalyst particles forming in the small pores of the support in the traditional method, and achieving rapid mass production and high active area of ​​platinum carbon catalysts with small size and uniform particle size.

CN117599782BActive Publication Date: 2025-04-18SUZHOU HYDROGINE POWER TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311866991.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-04-18
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

It is difficult to simply and effectively prepare platinum carbon catalysts with small sizes and uniform particle sizes in the prior art, and the traditional method has the problem of nanometal particles forming in small pores of the support, reducing the accessibility of the particles.

Method used

Using a combination of microflower technology and ultraviolet irradiation, the tetravalent platinum salt is reduced in stages to form a divalent platinum salt, and then heat-treated with the carbon support to generate platinum particles with small size and uniform particle size.

Benefits of technology

The rapid mass production of platinum carbon catalyst is achieved, with small and uniform particles and high active area, which simplifies the preparation process, avoids the nucleation induction period in traditional methods, and increases the nucleation rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117599782B_ABST
    Figure CN117599782B_ABST
Patent Text Reader

Abstract

The embodiment of the present application provides a platinum-carbon catalyst and a preparation method thereof, which relates to the field of catalysts. The preparation method of the platinum-carbon catalyst comprises the following steps: S1, allowing a tetravalent platinum salt solution to enter a first microchannel, and using ultraviolet light irradiation treatment to reduce the tetravalent platinum salt to a divalent platinum salt; S2, allowing the divalent platinum salt and the carrier dispersion to enter the second microchannel through a three-way valve respectively, and heat treatment is performed to reduce the divalent platinum salt to generate platinum particles and load them on a carbon carrier. The platinum-carbon catalyst and the preparation method thereof of the embodiment of the present application have a simple process, can prepare a small-sized platinum-carbon catalyst with uniform particle size, and the catalyst has a high active area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalysts, and in particular, to a platinum-carbon catalyst and a preparation method thereof. Background Art

[0002] At present, supported precious metal catalysts represented by platinum-carbon catalysts are one of the most widely used catalysts in industry. Due to the high cost of precious metals, there is an urgent need for simple methods to prepare supported precious metal catalysts with better performance.

[0003] In the traditional preparation method of supported catalysts, the active metal is first diffused onto the carrier by impregnation, adsorption or incipient wetness, and then calcined and reduced to obtain nano-metal particles. However, the formation of nano-metal particles directly on the carrier limits the control and optimization of the physical properties of the catalyst; in addition, due to the action of capillary forces, nano-metal particles tend to form in the small pores of the carrier, thereby reducing the accessibility of nano-metal particles.

[0004] The colloidal method breaks through the above limitations of traditional preparation methods. The colloidal method is to reduce soluble metal precursor salts in a solvent to form metal particles, which are then deposited on a carrier. The size of the metal particles is controllable, and the metal particle deposition occurs on the outer surface of the carrier, which increases the accessibility of the metal reactants and can more effectively utilize the metal particles.

[0005] For the colloidal method of synthesizing precious metal particles, additives such as surfactants, polymers or biomolecules are usually used, but these additives will block the active sites and need to be removed by thermal annealing or washing with hazardous chemicals, which is time-consuming and labor-intensive. If surfactants are not used, high-viscosity solvents are required to obtain stable colloidal solutions, washing steps are also required to collect the products, and reagents that may poison the catalyst (such as hydrochloric acid) may need to be added, which increases the complexity of catalyst preparation.

[0006] In summary, a simple method for preparing small-sized platinum-carbon catalysts with uniform particle size has not yet been found. Summary of the invention

[0007] The purpose of the embodiments of the present application is to provide a platinum-carbon catalyst and a preparation method thereof, which has a simple process and can prepare a small-sized platinum-carbon catalyst with uniform particle size, and the catalyst has a high active area.

[0008] In a first aspect, the present invention provides a method for preparing a platinum-carbon catalyst, which comprises the following steps:

[0009] S1, allowing a tetravalent platinum salt solution to enter the first microchannel, and treating it with ultraviolet light to reduce the tetravalent platinum salt to a divalent platinum salt;

[0010] S2, allowing the divalent platinum salt and the carrier dispersion to enter the second microchannel through the three-way valve respectively, and performing heat treatment to reduce the divalent platinum salt to generate platinum particles and load them on the carbon carrier.

[0011] In the above technical scheme, the tetravalent platinum salt is first aged by ultraviolet light and reduced to a divalent precursor platinum salt, and then a carbon carrier is added for reduction loading, so that the divalent platinum salt is further reduced to generate platinum particles, and deposited on the carbon carrier. The overall reaction process is simple, and this staged reduction method avoids the induction period of particle nucleation, increases the nucleation rate, greatly improves the reaction time, accelerates nucleation, and can quickly mass-produce small-sized and narrowly distributed platinum particles, thereby preparing small-sized and uniformly sized platinum-carbon catalysts with high active areas.

[0012] Among them, ultraviolet light irradiates the tetravalent platinum salt solution to generate free radicals with high reducing ability, thereby causing a reduction reaction, which can replace thermal energy as a driving force to kinetically avoid the sintering process. In addition, the flow rate of the tetravalent platinum salt solution is controlled by a microchannel, so that as much of the tetravalent platinum salt as possible is reduced to a divalent platinum salt, and the flow rate of the mixed solution is controlled by a microchannel, so that as much of the divalent platinum salt as possible is reduced.

[0013] In a possible implementation, in step S1, the intensity of the ultraviolet light is 60-90w, and can be 60-80w; the ultraviolet light irradiation time is related to the flow rate of the tetravalent platinum salt solution, and the flow rate of the tetravalent platinum salt solution is 1-10ml / min. By controlling the flow rate and the length and inner diameter of the first microchannel, the ultraviolet light irradiation treatment time can be 20-40min, and can be 20-35min.

[0014] In the above technical scheme, by controllable irradiation of ultraviolet light, specifically controlling the intensity and irradiation time, the tetravalent platinum salt is reduced to a divalent platinum salt, reducing excessive aging, and then further reduction loading is carried out, which effectively avoids the nucleation induction period in the reaction, thereby increasing the nucleation rate and greatly improving the reaction time, thereby obtaining particles with small size and narrower distribution size.

[0015] In a possible implementation, in step S2, the temperature of the heat treatment is 60-90° C., and the time of the heat treatment is related to the flow rate of the carbon carrier dispersion liquid, which is 1-50 ml / min, preferably 20-50 ml / min. By controlling the flow rate and the length and inner diameter of the second microchannel, the time of the heat treatment can be 5-180 min, preferably 5-60 min.

[0016] In the above technical solution, by controlling the heat treatment conditions, the divalent platinum salt can be reduced to platinum particles, and the heat treatment conditions can reduce the impact on the system and simplify the preparation of the catalyst.

[0017] In a possible implementation, the tetravalent platinum salt is selected from at least one of chloroplatinic acid, dinitrodiammineplatinum, platinum tetrachloride, and potassium chloroplatinate;

[0018] And / or, the mass ratio of platinum in the tetravalent platinum salt to the carbon carrier is 1:0.67-1:4.

[0019] In the above technical solution, the mass ratio of platinum in the raw material to the carbon carrier is controlled, so that the platinum particles can be evenly dispersed on the surface of the carbon carrier and the active area of ​​the catalyst can be increased.

[0020] In a possible implementation, the inner diameter of the first microchannel is 1.6-4 mm, and the length is 10-30 m; the inner diameter of the second microchannel is 1.6-4 mm, and the length is 30-70 m.

[0021] In the above technical solution, by setting the tube length and inner diameter of the first microfluidic channel and the second microfluidic channel within the above range, the ultraviolet light irradiation time and the heat treatment time can be easily controlled.

[0022] In a possible implementation, step S1 includes:

[0023] uniformly mixing the tetravalent platinum salt and the solvent to form the tetravalent platinum salt solution;

[0024] The tetravalent platinum salt solution enters the first microchannel through a first peristaltic pump and is irradiated with ultraviolet light.

[0025] In the above technical scheme, the flow rate of the tetravalent platinum salt solution can be controlled by a peristaltic pump, so that the tetravalent platinum salt solution can be continuously delivered to the microchannel at an appropriate flow rate for ultraviolet light irradiation, so that the tetravalent platinum salt is reduced and aged, thereby realizing continuous processing of the tetravalent platinum salt solution.

[0026] In one possible implementation, the mass ratio of platinum in the tetravalent platinum salt to the solvent is 1:1-1:10, and ultrasonic mixing is performed for 30-120 minutes to obtain the tetravalent platinum salt solution. Optionally, the solvent is selected from at least one of methanol, ethylene glycol, formaldehyde, formic acid, and ethanol.

[0027] In a possible implementation, step S2 includes:

[0028] preparing a carbon support and a reducing agent into a support dispersion;

[0029] The carrier dispersion and the divalent platinum salt are respectively introduced into the second microchannel through a three-way valve and then subjected to heat treatment.

[0030] In the above technical scheme, the carrier dispersion liquid and the divalent platinum salt solution are respectively continuously introduced into the second microchannel through the three-way valve, the carrier dispersion liquid and the divalent platinum salt solution are uniformly mixed into a mixed liquid in the three-way valve and enter the second microchannel, and then the mixed liquid in transportation is heat-treated to further reduce the divalent platinum salt, thereby realizing continuous processing of the mixed liquid.

[0031] In one possible implementation, the mass ratio of the carbon carrier to the reducing agent is 1:50-1:200, and ultrasonic mixing is performed for 30-120 minutes to obtain the carrier dispersion. Optionally, the reducing agent is selected from at least one of ethylene glycol, methanol, ethanol, formaldehyde, formic acid, and N,N-dimethylformamide.

[0032] In a second aspect, an embodiment of the present application provides a platinum-carbon catalyst, which is prepared using the preparation method of the platinum-carbon catalyst provided in the first aspect.

[0033] In the above technical solution, the platinum-carbon catalyst has small and uniform particles and a high active area, and is suitable for application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 TEM image of the platinum-carbon catalyst of Example 1;

[0036] Figure 2 This is the TEM image of the platinum-carbon catalyst of Comparative Example 3. DETAILED DESCRIPTION

[0037] For supported noble metal catalysts, given the metal, the performance of the supported catalyst depends primarily on the following physical properties: 1) particle size, 2) size distribution, and 3) distribution and location of the metal particles on the support. Since the surface-to-volume ratio of the catalyst particles increases as the particle size decreases, smaller particles generally have higher mass metal activity.

[0038] At present, the impregnation method is mostly used to prepare platinum-carbon catalysts. This method involves multiple steps, each of which is time-consuming and labor-intensive, and it takes at least several days to produce the finished catalyst. It has been found that the colloid method can be used to prepare supported catalysts, but it is difficult to achieve mass production of high-performance catalysts. The applicant found that the following two points should be noted when using the colloid method to mass-produce high-performance catalysts: 1. The concentration of the metal precursor should not be too low, so as not to cause problems such as excessive solvent volume, excessive waste generation and high operating costs. Therefore, the liquid phase system of the colloid should be able to fully adapt to high concentrations of precursor concentrations, and no particle sintering should occur. 2. The reaction steps should not be cumbersome. The more cumbersome the overall operation process is, the more complex the influencing factors are, and it is difficult to obtain high reproducibility, which is not desirable for industrial mass production.

[0039] After extensive research, the applicant discovered a method for mass production of high-performance platinum-carbon catalysts using a colloid method.

[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0041] The platinum-carbon catalyst and its preparation method according to the embodiments of the present application are described in detail below.

[0042] The present invention provides a method for preparing a platinum-carbon catalyst, which comprises the following steps:

[0043] S1. Allow a tetravalent platinum salt (precursor) solution to enter the first microchannel and treat it with ultraviolet light to reduce the tetravalent platinum salt to a divalent platinum salt.

[0044] The intensity of the ultraviolet light is 60-90w, and can be 60-80w; the ultraviolet light irradiation time is related to the flow rate of the tetravalent platinum salt solution, and the flow rate of the tetravalent platinum salt solution is 1-10ml / min. By controlling the flow rate and the length and inner diameter of the first microchannel, the ultraviolet light irradiation treatment time can be 20-40min, and can be 20-35min. In some embodiments of the present application, the inner diameter of the first microchannel is 1.6-4mm, and the length is 10-30m.

[0045] S2. Allow the divalent platinum salt solution and the carrier dispersion to enter the second microchannel through the three-way valve respectively, and perform heat treatment to reduce the divalent platinum salt to generate platinum particles and uniformly load them on the carbon carrier.

[0046] The temperature of the heat treatment is 60-90°C, and the time of the heat treatment is related to the flow rate of the carbon carrier dispersion, which is 1-50 ml / min. By controlling the flow rate and the length and inner diameter of the second microchannel, the time of the heat treatment can be 5-180 min. In some embodiments of the present application, the inner diameter of the second microchannel is 1.6-4 mm and the length is 30-70 m.

[0047] In an embodiment of the present application, the tetravalent platinum salt is selected from at least one of chloroplatinic acid, dinitrosodiammineplatinum, platinum tetrachloride, and potassium chloroplatinate; the mass ratio of platinum in the tetravalent platinum salt to the carbon carrier is 1:0.67-1:4.

[0048] S3, filtering and drying the reaction solution obtained by the treatment to obtain a platinum-carbon catalyst.

[0049] In the embodiments of the present application, the completion of the reaction can be verified by collecting the filtrate. Specifically, sodium borohydride is added to the filtrate to observe the color change. If the color of the filtrate turns black, it means that the aforementioned reaction is incomplete. If the filtrate remains clear and does not change color, it means that the aforementioned reaction is complete.

[0050] In some embodiments of the present application, step S1 includes:

[0051] S11, uniformly mixing a tetravalent platinum salt and a solvent to form a tetravalent platinum salt solution.

[0052] The mass ratio of platinum in the tetravalent platinum salt to the solvent is 1:1-1:10, and ultrasonic mixing is performed for 30-120 minutes to obtain a tetravalent platinum salt solution. Optionally, the solvent is selected from at least one of methanol, ethylene glycol, formaldehyde, formic acid, and ethanol.

[0053] S12, passing the tetravalent platinum salt solution into the first microchannel through a peristaltic pump, controlling the flow rate of the tetravalent platinum salt solution to 1-10 ml / min through the peristaltic pump, and reducing the tetravalent platinum salt to a divalent platinum salt by ultraviolet irradiation.

[0054] In the above process, the tetravalent platinum salt solution enters the peristaltic pump through the inlet of the peristaltic pump, then enters the first microchannel through the outlet of the peristaltic pump, and is transported to the first microchannel at a certain flow rate under the action of the peristaltic pump, and is irradiated by ultraviolet light in the first microchannel. As an embodiment, the outlet of the peristaltic pump is connected to a spiral quartz pipe as the first microchannel, and the ultraviolet light irradiates the quartz pipe.

[0055] By controlling the flow rate of the solution through a peristaltic pump and setting the inner diameter specification and length of the quartz tube, the time for the tetravalent platinum salt solution to pass through the quartz tube can be controlled; in the case where the tetravalent platinum salt solution is continuously transported and ultraviolet light continuously irradiates the entire quartz tube, the time of ultraviolet light irradiation treatment refers to the time for the tetravalent platinum salt solution to pass through the quartz tube.

[0056] In some embodiments of the present application, step S2 includes:

[0057] S21, preparing a carbon carrier and a reducing agent into a carrier dispersion;

[0058] The mass ratio of the carbon carrier to the reducing agent is 1:50-1:200, and ultrasonic mixing is performed for 30-120 minutes to obtain a carrier dispersion. Optionally, the reducing agent is selected from at least one of ethylene glycol, methanol, ethanol, formaldehyde, formic acid, and N,N-dimethylformamide.

[0059] S22. The carrier dispersion and the reaction solution of the divalent platinum salt enter the second microchannel through the three-way valve respectively, and the flow rate of the carbon carrier dispersion is controlled to 1-50 ml / min by the second peristaltic pump, and then heat-treated to reduce the divalent platinum salt to generate platinum particles and evenly load them on the carbon carrier.

[0060] In the above process, the divalent platinum salt reaction liquid and the carrier dispersion liquid enter the microchannel through the three-way valve respectively, and the carbon carrier dispersion liquid enters the three-way valve at a flow rate of 1-50 ml / min through the second peristaltic pump, and enters the second microchannel after mixing with the divalent platinum salt reaction liquid entering the three-way valve at a flow rate of 1-10 ml / min, and undergoes heat treatment during the transportation process in the second microchannel. As an embodiment, the outlets of the first peristaltic pump and the second peristaltic pump are respectively connected to a spiral heat conduction pipeline, i.e., the second microchannel, through the three-way valve, and the heat conduction pipeline is immersed in a high-temperature medium (such as water) at a predetermined temperature.

[0061] By controlling the flow rate of the solution through a peristaltic pump and setting the inner diameter specification and length of the heat transfer pipeline, the time for the mixed solution of the divalent platinum salt reaction solution and the carrier dispersion solution to pass through the heat transfer pipeline can be controlled; when the mixed solution is continuously transported and the heat transfer pipeline is completely immersed in the high-temperature medium, the heat treatment time refers to the time for the mixed solution to pass through the heat transfer pipeline.

[0062] In an embodiment of the present application, different peristaltic pumps are used in step S1 and step S2, and are connected into a continuous production equipment through a three-way valve. Specifically, the outlet of the first peristaltic pump in step S1 is connected to the inlet of the quartz pipe, the outlet of the quartz pipe is connected to one inlet of the three-way valve, the outlet of the second peristaltic pump is connected to the other inlet of the three-way valve, the outlet of the three-way valve is connected to the inlet of the heat transfer pipe, the quartz pipe is correspondingly provided with an ultraviolet light irradiation device, and the heat transfer pipe is correspondingly provided with a high-temperature medium.

[0063] The production equipment can realize the continuous production of platinum-carbon catalysts: the tetravalent platinum salt solution continuously enters the quartz pipe (first microchannel) through the first peristaltic pump, and then undergoes ultraviolet light irradiation treatment; the carrier dispersion enters the three-way valve under the action of the second peristaltic pump, and is mixed with the ultraviolet light-treated reaction liquid entering the three-way valve and enters the heat pipe (second microchannel), and then undergoes heat treatment; the final reaction liquid is collected, filtered, and dried. This continuous production process can achieve gram-level production of catalysts within tens of minutes, and achieve mass production. The catalyst obtained has a high active area and meets application requirements.

[0064] In addition, an embodiment of the present application provides a platinum-carbon catalyst, which is prepared using the preparation method of the platinum-carbon catalyst of the aforementioned embodiment.

[0065] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0066] Example 1

[0067] This embodiment provides a platinum-carbon catalyst, which is prepared using the following production equipment and according to the following process:

[0068] The production equipment includes: a first peristaltic pump, a spiral quartz tube (first microchannel), a three-way valve, a second peristaltic pump and a spiral heat-conducting tube (second microchannel), the first peristaltic pump, the spiral quartz tube, the three-way valve and the spiral heat-conducting tube are connected in sequence, and the second peristaltic pump, the three-way valve and the spiral heat-conducting tube are connected in sequence. The length of the quartz tube is 20m, and the inner diameter is 3mm, and the length of the heat-conducting tube is 60m, and the inner diameter is 3mm. The outlet of the first peristaltic pump is connected to the inlet of the quartz tube, and the outlet of the quartz tube is connected to one inlet of the three-way valve, and the outlet of the second peristaltic pump is connected to the other inlet of the three-way valve, and the outlet of the three-way valve is connected to the inlet of the heat-conducting tube. The quartz tube is correspondingly provided with an ultraviolet lamp, and all the quartz tubes can be uniformly irradiated by ultraviolet light at the same time. The heat-conducting tube is correspondingly provided with a heating device, and the heating device is used to heat the high-temperature medium. All the heat-conducting tubes are immersed in the high-temperature medium so that they can be heated by the high-temperature medium.

[0069] Production process:

[0070] (1) Hexahydrate chloroplatinic acid and 100 g methanol were sampled in advance according to the ratio of Pt:methanol = 1:5, and ultrasonically mixed for 30 min to obtain a tetravalent precursor solution. Carbon support and ethylene glycol were sampled in advance according to the mass ratio of carbon support and ethylene glycol of 1:100, and ultrasonically mixed for 30 min to obtain 100 g support dispersion.

[0071] (2) The precursor solution enters from the inlet of the first peristaltic pump and, under the action of the first peristaltic pump, is continuously passed into the quartz tube for ultraviolet light irradiation. The intensity of the ultraviolet light is 80w. Then it enters the three-way valve. The flow rate of the precursor solution through the quartz tube is 5ml / min.

[0072] (3) The carrier dispersion enters from the inlet of the second peristaltic pump and continuously enters the three-way valve under the action of the second peristaltic pump. It is fully mixed with the precursor reaction liquid in step 2 under the action of the three-way valve and enters the heat transfer tube. The flow rate of the carrier dispersion is 40 ml / min, and the temperature of the heat treatment is controlled to be 80°C by the high-temperature medium.

[0073] (4) The reaction solution was collected, filtered, and dried in a vacuum drying oven at 80° C. for 12 h to obtain a platinum-carbon catalyst.

[0074] Verify whether the reaction of this example is complete: collect the clear and transparent filtrate, add 0.05 g of sodium borohydride to 20 ml of the filtrate and observe the color change. After 1 min, the filtrate remains clear and transparent, and does not change color after adding sodium borohydride, indicating that the reaction of this example is complete.

[0075] Example 2

[0076] This embodiment provides a platinum-carbon catalyst, which differs from Embodiment 1 in that the intensity of the ultraviolet light is 80w, and the flow rate of the precursor solution through the quartz tube is 10ml / min.

[0077] The completion of the reaction in this example was verified, and it was found that the filtrate remained clear and transparent, and did not change color upon addition of sodium borohydride, indicating that the reaction in this example was complete.

[0078] Example 3

[0079] This embodiment provides a platinum-carbon catalyst, which differs from Embodiment 1 in that the intensity of the ultraviolet light is 80w, and the flow rate of the precursor solution through the quartz tube is 4ml / min.

[0080] The completion of the reaction in this example was verified, and it was found that the filtrate remained clear and transparent, and did not change color upon addition of sodium borohydride, indicating that the reaction in this example was complete.

[0081] Example 4

[0082] This embodiment provides a platinum-carbon catalyst, which differs from Embodiment 1 in that the intensity of the ultraviolet light is 80w, and the flow rate of the precursor solution through the quartz tube is 1ml / min.

[0083] The completion of the reaction in this example was verified, and it was found that the filtrate remained clear and transparent, and did not change color upon addition of sodium borohydride, indicating that the reaction in this example was complete.

[0084] Example 5

[0085] This embodiment provides a platinum-carbon catalyst, which differs from Embodiment 1 in that the intensity of the ultraviolet light is 60w, and the flow rate of the precursor solution through the quartz tube is 5ml / min.

[0086] The completion of the reaction in this example was verified, and it was found that the filtrate remained clear and transparent, and did not change color upon addition of sodium borohydride, indicating that the reaction in this example was complete.

[0087] Example 6

[0088] This embodiment provides a platinum-carbon catalyst, which differs from Embodiment 1 in that the intensity of the ultraviolet light is 70w, and the flow rate of the precursor solution through the quartz tube is 5ml / min.

[0089] The completion of the reaction in this example was verified, and it was found that the filtrate remained clear and transparent, and did not change color upon addition of sodium borohydride, indicating that the reaction in this example was complete.

[0090] Example 7

[0091] This embodiment provides a platinum-carbon catalyst, which differs from Embodiment 1 in that the intensity of the ultraviolet light is 90w, and the flow rate of the precursor solution through the quartz tube is 5ml / min.

[0092] The completion of the reaction in this example was verified, and it was found that the filtrate remained clear and transparent, and did not change color upon addition of sodium borohydride, indicating that the reaction in this example was complete.

[0093] Example 8

[0094] This embodiment provides a platinum-carbon catalyst, which differs from Embodiment 1 in that the heat treatment temperature is 60° C. and the flow rate of the carrier dispersion is 20 ml / min.

[0095] The completion of the reaction in this example was verified, and it was found that the filtrate remained clear and transparent, and did not change color upon addition of sodium borohydride, indicating that the reaction in this example was complete.

[0096] Example 9

[0097] This embodiment provides a platinum-carbon catalyst, which differs from Embodiment 1 in that the heat treatment temperature is 90° C. and the flow rate of the carrier dispersion is 50 ml / min.

[0098] The completion of the reaction in this example was verified, and it was found that the filtrate remained clear and transparent, and did not change color upon addition of sodium borohydride, indicating that the reaction in this example was complete.

[0099] Comparative Example 1

[0100] This comparative example 1 provides a platinum-carbon catalyst, which is different from Example 1 in that no ultraviolet light irradiation is provided, and finally a platinum-carbon catalyst is obtained.

[0101] To verify whether the reaction of this comparative example is complete, it was found that the collected filtrate was yellow, and upon addition of sodium borohydride, the filtrate turned black, indicating that the platinum salt precursor was not aged in this comparative example and the reaction was incomplete.

[0102] Comparative Example 2

[0103] This comparative example 1 provides a platinum-carbon catalyst, which differs from Example 1 in that: in step (2), no ultraviolet light irradiation is provided, in step (3), the heat treatment temperature is controlled to 80°C, and ultraviolet light irradiation treatment is carried out simultaneously, and the flow rate of the carrier dispersion liquid is 40 ml / min, and finally a platinum-carbon catalyst is obtained.

[0104] To verify whether the reaction of this comparative example is complete, it was found that the collected filtrate was yellow. When sodium borohydride was added, the filtrate turned black, indicating that ultraviolet light irradiation was additionally set during the heat treatment of this comparative example. However, due to the strong absorption of light by the carbon carrier, the ultraviolet light could not work and the reaction was still incomplete.

[0105] Comparative Example 3

[0106] This comparative example 1 provides a platinum-carbon catalyst, which differs from Example 1 in that: in step (2), no ultraviolet light irradiation is provided, in step (3), the heat treatment temperature is controlled to be 80° C., the flow rate of the carrier dispersion liquid is 1 ml / min, and finally a platinum-carbon catalyst is obtained.

[0107] In order to verify whether the reaction of this comparative example is complete, it was found that the filtrate remained clear and transparent, indicating that when this comparative example is not subjected to precursor aging using ultraviolet light, a very long time is required for the complete reaction, and subsequent morphology testing showed that the obtained catalyst particles are not uniform in size.

[0108] 1. Physical performance test

[0109] The morphology and particle size distribution of the platinum-carbon catalysts of Examples 1-9 and Comparative Example 3 were detected. The TEM image of the platinum-carbon catalyst of Example 1 is as follows: Figure 1 As shown, the TEM image of the platinum-carbon catalyst of Comparative Example 3 is as follows Figure 2 The particle size distribution of each embodiment and comparative example is shown in Table 1.

[0110] Table 1 Particle size distribution comparison

[0111]

[0112] Depend on Figure 1-Figure 2 From Table 1, we can see that:

[0113] The catalyst particles obtained in Example 1 are small and uniform ( Figure 1 ), the variance of particle size distribution is small.

[0114] The reason for Examples 4 and 7 may be that the platinum precursor is over-aged, resulting in a portion of tetravalent platinum being directly reduced to elemental platinum and agglomerated on the carrier. Compared with Example 1, the uniformity of the particle size is poor.

[0115] Examples 2-3 and Examples 5-6 may have poorer particle size uniformity than Example 1 because the platinum precursor is not aged enough.

[0116] Comparative Example 1-2 is an unqualified sample due to incomplete reaction, and no performance test is required; although Comparative Example 3 can react completely, its particles are not uniform compared with Example 1 ( Figure 2 ), the variance of particle size distribution is large.

[0117] 2. Catalyst electrochemical performance test

[0118] The electrochemical tests were carried out on a CHI660E electrochemical station and a rotating disk electrode device produced by Shanghai Chenhua. The electrochemical performance tests of the catalysts were mainly cyclic voltammetry (CV) and linear sweep voltammetry (LSV). All electrode potentials in the experiments were normalized using a reversible hydrogen electrode (RHE).

[0119] (1) Preparation of working electrode

[0120] Weigh 8 mg of catalyst into a test tube, and pipette 2 ml of the prepared dispersion (a certain proportion of isopropanol, water, and 5 wt% Nafion solution). Ultrasonic disperse the mixed solution for 20 min to obtain a uniform catalyst ink. Then pipette 10 uL of the catalyst ink and drop it evenly on the pre-polished and cleaned gold electrode (area 0.196 cm 2 ) on it, wait for it to dry naturally to form a catalytic layer, and then you can get a working electrode.

[0121] 2) Electrochemical performance test

[0122] CV test: Place the electrodes in an electrolytic cell to form a three-electrode system. The reference electrode is Hg / Hg2SO4, the counter electrode is a platinum mesh electrode, and the electrolyte is a 0.5M H2SO4 solution saturated with N2 and kept at a constant temperature of 25°C. Open the software, set the scan rate in the CV test window to 50m / s, and scan 20 times (10 cycles) at -0.632 to 0.328V to fully activate the catalyst and stabilize the complex desorption peak. Calculate the electrochemical active area ECSA of the catalyst based on the data of the last cycle.

[0123] Linear sweep voltammetry: In order to evaluate the ORR electrocatalytic performance of the catalyst materials and their performance in the reaction process, cathode polarization measurements were performed and the linear sweep voltammetry (LSV) results were used for judgment. LSV test: The LSV test window was replaced with an O2-saturated 0.1M HC1O4 electrolytic cell (for IR compensation), and the working electrode was kept at a speed of 1600rpm. Scanning was performed at -0.26 to 0.695V at a scan rate of 10mV / s. The kinetic current density was calculated from the measured current density and the limiting current density, and the MA was calculated from the kinetic current density and the actual mass of the precious metal.

[0124] The electrochemical performances of the embodiments and comparative examples are shown in Table 2.

[0125] Table 2 Comparison of electrochemical performance

[0126]

[0127] The oxygen evolution activity and durability of the catalyst were studied by a series of electrochemical tests (cyclic voltammetry CV, linear sweep voltammetry LSV, etc.). In general, the electrochemical activity area ECSA and mass activity MA are used to judge the ORR performance. The electrochemical performance of the catalyst in the embodiment of the present application is good.

[0128] In summary, the platinum-carbon catalyst and the preparation method thereof of the embodiments of the present application have simple processes and can prepare platinum-carbon catalysts with small sizes and uniform particle sizes.

[0129] The above description is only an embodiment of the present application and is not intended to limit the protection scope of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a platinum-carbon catalyst, characterized in that: It includes the following steps: S1, allowing a tetravalent platinum salt solution to enter the first microchannel, and treating it with ultraviolet light to reduce the tetravalent platinum salt to a divalent platinum salt; S2, allowing the divalent platinum salt and the carrier dispersion to enter the second microchannel through the three-way valve respectively, and performing heat treatment to reduce the divalent platinum salt to generate platinum particles and load them on the carbon carrier.

2. The method for preparing a platinum-carbon catalyst according to claim 1, characterized in that: In step S1, the intensity of the ultraviolet light is 60-90w; the time of the ultraviolet light irradiation treatment is 20-40min; And / or, the flow rate of the tetravalent platinum salt solution is 1-10 ml / min.

3. The method for preparing a platinum-carbon catalyst according to claim 2, characterized in that: The intensity of the ultraviolet light is 60-80w; the time of the ultraviolet light irradiation treatment is 20-35min.

4. The method for preparing a platinum-carbon catalyst according to claim 1, characterized in that: In step S2, the temperature of the heat treatment is 60-90°C, and the time of the heat treatment is 5-180 minutes. And / or, the flow rate of the carrier dispersion is 1-50 ml / min.

5. The method for preparing a platinum-carbon catalyst according to claim 1, characterized in that: The tetravalent platinum salt is selected from at least one of chloroplatinic acid, dinitrosodiammineplatinum, platinum tetrachloride, and potassium chloroplatinate; And / or, the mass ratio of platinum in the tetravalent platinum salt to the carbon carrier is 1:0.67-1:

4.

6. The method for preparing a platinum-carbon catalyst according to claim 1, characterized in that: The inner diameter of the first microchannel is 1.6-4 mm and the length is 10-30 m; And / or, the inner diameter of the second microchannel is 1.6-4 mm, and the length is 30-70 m.

7. The method for preparing a platinum-carbon catalyst according to claim 1 or 6, characterized in that: Step S1 includes: uniformly mixing the tetravalent platinum salt and the solvent to form the tetravalent platinum salt solution; The tetravalent platinum salt solution is introduced into the first microfluidic channel through a first peristaltic pump.

8. The method for preparing a platinum-carbon catalyst according to claim 7, characterized in that: The mass ratio of platinum in the tetravalent platinum salt to the solvent is 1:1-1:10, and ultrasonic mixing is performed for 30-120 minutes to obtain the tetravalent platinum salt solution.

9. The method for preparing a platinum-carbon catalyst according to claim 8, characterized in that: The solvent is selected from at least one of methanol, ethylene glycol, formaldehyde, formic acid and ethanol.

10. The method for preparing a platinum-carbon catalyst according to claim 1 or 6, characterized in that: Step S2 includes: preparing the carbon carrier and the reducing agent into the carrier dispersion; The carrier dispersion and the divalent platinum salt are respectively introduced into the second microchannel through a three-way valve and then subjected to heat treatment.

11. The method for preparing a platinum-carbon catalyst according to claim 10, characterized in that: The mass ratio of the carbon carrier to the reducing agent is 1:50-1:200, and ultrasonic mixing is performed for 30-120 minutes to obtain the carrier dispersion.

12. The method for preparing a platinum-carbon catalyst according to claim 11, characterized in that: The reducing agent is selected from at least one of ethylene glycol, methanol, ethanol, formaldehyde, formic acid, and N,N-dimethylformamide.

Citation Information

Patent Citations

  • Platinum-carbon catalyst and preparation method thereof

    CN114308023A